Piecemeal Rupture of the Mentawai Patch, Sumatra: The 2008 Mw 7.2 North Pagai Earthquake Sequence. Issue 11 (27th November 2017) - Salman, Rino; Hill, Emma M.; Feng, Lujia; Lindsey, Eric O.; Mele Veedu, Deepa; Barbot, Sylvain; Banerjee, Paramesh; Hermawan, Iwan; Natawidjaja, Danny H.
Abstract: The 25 February 2008 M w 7.2 North Pagai earthquake partially ruptured the middle section of the Mentawai patch of the Sunda megathrust, offshore Sumatra. The patch has been forecast to generate a great earthquake in the next few decades. However, in the current cycle the patch has so far broken in a sequence of partial ruptures, one of which was the 2008 event, illustrating the potential of the patch to generate a spectrum of earthquake sizes. We estimate the coseismic slip distribution of the 2008 event by jointly inverting coseismic offsets from GPS and interferometric synthetic aperture radar. We then estimate afterslip with 5.6 years of cumulative GPS displacements. Our results suggest that the estimated afterslip partially overlaps the coseismic rupture. The overlap of coseismic rupture and afterslip can be explained conceptually by a simple rate‐and‐state model where the degree of overlapping is controlled by the dynamic weakening and the critical nucleation size in the velocity‐weakening area. Comparing our rate‐and‐state model results with our geodetic inversion results, we suggest that the part of the coseismic rupture that does not overlap with the afterslip may represent a velocity‐weakening region, while the overlapping part may represent a velocity‐strengthening region. Key Points: We present the first detailed study of the 2008 M w 7.2 North Pagai earthquake using GPS and InSAR data The 2008 earthquake sequence ruptured only partially the middle section of the Mentawai patch The estimated afterslip partially overlaps the updip region of the coseismic rupture area